-(8y+1)-(-7y-5)=3

Simple and best practice solution for -(8y+1)-(-7y-5)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(8y+1)-(-7y-5)=3 equation:


Simplifying
-1(8y + 1) + -1(-7y + -5) = 3

Reorder the terms:
-1(1 + 8y) + -1(-7y + -5) = 3
(1 * -1 + 8y * -1) + -1(-7y + -5) = 3
(-1 + -8y) + -1(-7y + -5) = 3

Reorder the terms:
-1 + -8y + -1(-5 + -7y) = 3
-1 + -8y + (-5 * -1 + -7y * -1) = 3
-1 + -8y + (5 + 7y) = 3

Reorder the terms:
-1 + 5 + -8y + 7y = 3

Combine like terms: -1 + 5 = 4
4 + -8y + 7y = 3

Combine like terms: -8y + 7y = -1y
4 + -1y = 3

Solving
4 + -1y = 3

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -1y = 3 + -4

Combine like terms: 4 + -4 = 0
0 + -1y = 3 + -4
-1y = 3 + -4

Combine like terms: 3 + -4 = -1
-1y = -1

Divide each side by '-1'.
y = 1

Simplifying
y = 1

See similar equations:

| x+0.13x=37300 | | 2x(x-5)=6x^2-11x | | 13+3n=8n+8 | | 3x^2+2x=-1 | | 10z-5+3=8-z | | 5.7q-4.5-4.9q=-0.2q-4.9 | | 2(3b-2)-5b=4(b-1)+8b | | -4(5-3z)=3z+61 | | -.11(x-27)+.33(x+3)=x+4 | | x+.13=373 | | x+2x+3=12 | | 6y=18-3y | | 25x^2-1=o | | 31000n=38000n | | 3x+5=7x-4 | | (u-4)(u-4)=2u^2-17u+30 | | 7x+5=3x+4 | | -5x+7=3x-41 | | -13=h-7 | | 5t-(-9)t^2=0 | | 54x^3-128y^3=0 | | -10z+7=8+6z | | -5(2p+2)-7=3(2p+5) | | -7x-3=52+4x | | -10-3x-2x=15 | | 3y-3+y+19=8y+20-6y | | 9+2z-5=9z+9-6z | | -5(1-5x)+5(8x-2)=11x-8x | | 4x^3-9x^2-9x=0 | | 7x+10+7x=24 | | -3x-20=2x+95 | | -6.8-3z-2.5-z=-3z+0.4 |

Equations solver categories